May Energy Justice Enhance Human Rights Protection in the European Union? - Lucia Mokrá; Donald Wertlen (Bratislava Law Review)
Energy justice, sustainable environment and human rights became the leading factors of some of the sustainable development goals set as the common goal of international community. The contemporary greening process is interconnecting with number of transformations in decision-making and policies. Greening process and its integral part, access to energy as the tool for preventing energy poverty is related with human rights. We assume, that access to energy is fundamental to meet basic human needs and existing human rights necessitates access to energy. The European Union is perceived as the key regional leader in greening process, by adoption of EU Green Deal. At the same time, the European Union has also the ambition to be human rights actor. Both these goals are led by declarations of the European Union and obligations of its Member States internationally. The paper presents outcomes of quantitative and qualitative research focused on the question, how the energy justice is conditioning the effective exercise of other rights guaranteed by international human rights treaties, within the European Union environment.